2021
DOI: 10.1038/s41598-021-84149-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogenic genes in Campylobacter jejuni isolated from broiler carcasses and broiler slaughterhouses

Abstract: Campylobacter jejuni is one of the most common causes of foodborne diseases worldwide. There are few reports on Campylobacter strains isolated from Latin-American countries. Here, 140 C. jejuni strains isolated from cloacal and transport boxes swabs, water from chiller tanks, and broiler carcasses of five poultry companies in Southern Brazil were identified using phenotypic and genotypic methods. Polymerase chain reaction (PCR) was used to analyze eight C. jejuni virulence markers: flaA, cadF, and invasion-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
4
19
1
Order By: Relevance
“…The prevalence of the wlaN gene is controversial within the literature. A low prevalence was reported in the Campylobacter strains from Japan [83], Bangladesh [62], Ireland [84], and Brazil [85], whereas a study in Korea identified the wlaN gene among 100% of human and 78.6% of animal C. jejuni isolates investigated [86]. The mass screening of C. jejuni genomes presented here showed that the average prevalence of this gene in the world is about 56%.…”
Section: Discussionmentioning
confidence: 62%
“…The prevalence of the wlaN gene is controversial within the literature. A low prevalence was reported in the Campylobacter strains from Japan [83], Bangladesh [62], Ireland [84], and Brazil [85], whereas a study in Korea identified the wlaN gene among 100% of human and 78.6% of animal C. jejuni isolates investigated [86]. The mass screening of C. jejuni genomes presented here showed that the average prevalence of this gene in the world is about 56%.…”
Section: Discussionmentioning
confidence: 62%
“…In the case of campylobacteriosis, both successful invasion and organization in host cells depend on various virulence factors linked with adhesion to intestinal mucosa, invasion of epithelial cells, toxin production, and protein secretion [14]. Among adhesion-associated markers, the following are crucial: the flaA gene, encoding the major flagellin protein (FlaA), a structural component of flagella crucial for attachment to intestinal epithelial cells and involved in autoagglutination and microcolony formation [15,16]; the cadF gene, encoding a fibronectin binding protein CadF [17]; the racR gene, encoding a DNA-binding response regulator [18]; a periplasmic cytochrome C peroxidase, encoded by docA; and the chaperone protein DnaJ, encoded by the dnaJ gene [19]. Regarding markers affecting invasion, a significant role is played by the pldA gene, encoding phospholipase A; the ciaB gene, encoding a Campylobacter invasion antigen; the virB11 gene, responsible for host cell invasion; and invasion-associated marker (iam) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that most flocks arrive to the slaughterhouse with Campylobacter . Positive cloacal swabs at the reception of slaughterhouses show that broilers were contaminated on the farm ( Borges et al, 2020 ; Sierra-Arguello et al, 2021 ; Perdoncini et al, 2022 ). Since the probability of a broiler to become colonized increases during rearing, it is estimated that 60–80% of the flocks may be Campylobacter -positive at slaughter age ( Hermans et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of Campylobacter spp. by conventional isolation was performed according to the methodology described by Sierra-Arguello et al (2021) . An aliquot (1 mL) of each sample was homogenized in Bolton broth (9 mL) (Oxoid) supplemented with antimicrobials (cefoperazone 20 mg/L, vancomycin 20 mg/L, trimethoprim 20 mg/L, and cycloheximide 50 mg/L; SR0183, Oxoid) and incubated under microaerophilic conditions using a gas tank with a mixture of 10% CO 2 , 5% O 2 , and 85% N 2 for 48 h at 41.5°C.…”
Section: Methodsmentioning
confidence: 99%